Mended - A Aravind (Nanyang Technological University, 2022)
Mended is a 13 minute short film Final Year Project (FYP) produced by Hantu Haus Films. The short film was produced by A Aravind, Alia Alkaff, Clarice Teh and Pang Hao Cher, a group of undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication & Information (WKWSCI), under the supervision of Associate Professor Ian Dixon.